A STUDY OF INSTRUMENT-RELATED ILLUSTRATIONS ON BOOK COVERS BY CONTEMPORARY ARTIST SANDEEP RASHINKAR - Kulkarni, Bhagyashree; Bhardwaj, Kumkum (International Journal of Research -GRANTHAALAYAH, 2026)
Illustration, drawing, painting, photography, or the presentation of art in various forms represents a mode of visual expression rooted in human perception. It is created to provide a graphic and visual representation that clearly interprets or defines sensory information. Contemporary artist Sandeep Rashinkar has created numerous artworks, including book cover illustrations. A book cover is a distinct art form in which the artist visually represents the story, theme, and emotions of a book through imagery on its cover. This not only attracts readers’ attention but also enables them to intuitively sense the underlying message and essence of the book. The book cover establishes the identity of the book and gives unified form to the ideas of both the artist and the author. The artist has illustrated book covers on a variety of themes such as education, work, dance, music, and women. In particular, he has beautifully depicted musical instruments in several cover illustrations related to music. The primary objective of this research paper is to conduct an artistic study of instrument-related illustrations depicted on book covers. For this research work, the personal interview method has been employed.